Jamur Mikoriza Vesikular Arbuskular (MVA) pada Perakaran Tanaman Bawang Mekah (Eleutherine americana Merr.) - Irwan Lovadi,, Hadi Saputra, Rizalinda, (Universitas Tanjungpura, 2015)
Arbuscular vesicular mycorhizae (AVM) is a fungus that has mutualistic symbiosis with plant roots. Arbuscular vesicular mycorhizae (AVM) has ability to boost plant growth but information regarding this types of fungi at Mecca onion (Eleutherine americana) is still unknown. This study aims to determine the type of arbuscular vesicular mycorhizae (AVM) and level of infection at rooting of Mecca onion (E. americana). This research was conducted in Laboratory of Microbiology, Faculty of Mathematics and Natural Sciences, University of Tanjungpura from July 2014 to September 2014. The analysis of soil samplewas conducted at the Laboratory of Chemistry and Soil Fertility, Faculty of Agriculture, University of Tanjungpura. Isolation of soil samples employed two techniques, wet filter chamber and centrifugation. The study found that as many as 277 arbuscular vesicular mycorhizae (AVM) spores derived from genus Glomus(9 types), Acaulospora (3 types) and Paraglomus (1 type). The observation of root preparation indicated that structure of arbuscular vesicular mycorhizae (AVM) contained spores and hyphae with the percentage of root infection was 12,5%, and it is classified into low category.